Applying the hidden treasures of population biodiversity to decision making and management. (December 2015) - Volckaert, Filip A.M.
Abstract: The justified interest for nature and the environment is being implemented in a growing set of guidelines, agreements and laws involving political entities from a global to regional scale. Key is the concept of biodiversity which is addressed at three levels: ecosystems, species and populations. So far societal and political focus has largely been on species with limited attention being paid to the dynamic component of biodiversity as represented in populations and their genes. The information extracted from the genes and genomes of marine populations is accessible in five formats: (i) genotypes as biological markers to trace individuals and to establish parent-offspring relationships; (ii) the diversity of genes; (iii) the measurement of the impact of chance due to low numbers; (iv) the degree of distinctness of populations; and (v) the potential to adapt. These five formats show the possibilities for monitoring the heritable health status of the marine environment in order to assist governance and management.